Imaginative criminology : of spaces past, present and future - Seal, Lizzie, 1977-; O'Neill, Maggie (New horizons in criminology., 2019)
Founded in cultural, textual, and ethnographic analysis, this distinctive and engaging book proposes an imaginative criminology, focusing on how spaces of transgression, control or confinement are lived, portrayed and imagined.